Preoperative anxiety: Is it affected by preoperative counseling and surgical technique? - Syed F. Javaid; Hamed Aljanaahi; Saleh AlSeiari; Dana Aljaberi; Taif Aleissaee; Ahmed Mohammed; Fayez T. Hammad (PLoS ONE, 2026)
Background Preoperative anxiety (PA) is a common psychological response that can adversely affect patient satisfaction and surgical complications and outcomes. To reduce these effects, several studies were conducted to identify the factors that influence the severity of PA; however; none of the studies have examined the relationship between the PA and factors related to preoperative surgical and anesthetic counseling and the type of surgical technique. Methods A cross-sectional questionnaire-based study was carried out between November 2023-January 2024, involving patients aged 18 years or older who were scheduled for surgical procedures at our institute. Anxiety levels were assessed using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). PA was stratified into low (<11) and high (≥11) anxiety based on the total anxiety (both anesthesia- and surgery-related) scores. Results The prevalence of clinically significant PA was 39.7%. In addition to the previously identified factors such as female gender, younger age and unemployment status, other factors which were also associated with higher PA included fewer pre-operative surgical consultations, longer duration of each surgical consultation, undergoing laparoscopic procedures instead of open surgery, referral to an internist for further evaluation of preexisting medical conditions and use of general anesthesia or uncertainty about the type of anesthesia (P < 0.05 for all). However, the number of anesthetic consultations and the surgeon’s level of experience were not significantly associated with PA. Interestingly, using illustrations and figures during consultations was also associated with higher PA (P < 0.05) while searching the internet for more information, did not have an effect. Conclusions Preoperative anxiety remains a significant concern and was associated with factors related to gender, employment status, preoperative surgical and anesthetic counseling, surgical technique and type of anesthesia. These findings might help in formulating targeted interventions to reduce preoperative anxiety and improve surgical outcomes.